Real-World Effectiveness of Dupilumab in Adult and Adolescent Patients with Atopic Dermatitis: 2-Year Interim Data from the PROSE Registry - Eric L. Simpson; Ben Lockshin; Lara Wine Lee; Zhen Chen; Moataz Daoud; Andrew Korotzer (Adis, Springer Healthcare, 2024)
Abstract Introduction There is a scarcity of data beyond 1 year for the use of dupilumab to treat atopic dermatitis (AD) in a real-world setting. This study aimed to evaluate the 2-year effectiveness of dupilumab among adult and pediatric patients with moderate-to-severe AD included in a real-world, longitudinal database study. Methods PROSE is an ongoing, prospective, observational, multi-center registry in the USA and Canada, designed to collect real-world data from patients aged ≥ 12 years with moderate-to-severe AD who initiate dupilumab in accordance with country-specific prescribing information. Assessments include body surface area affected by AD (BSA), Eczema Area and Severity Index (EASI), Dermatology Life Quality Index (DLQI), Pruritus Numerical Rating Scale (P-NRS), Patient-Oriented Eczema Measure (POEM), Patient Global Assessment of Disease (PGAD) questionnaire score, and occurrence of adverse events (AEs). Results Of 764 patients who enrolled in PROSE, 632 (83%) remained in the study at the time of this interim analysis. Improvements were observed at the first post-baseline clinic visit (approximately 3 months) in the clinician-assessed measures (mean BSA and EASI scores); improvements were sustained throughout the 2-year period covered in the present study. Consistent and sustained improvements were also observed over the 2-year period in the patient-reported measures of P-NRS, POEM, and DLQI, and in the proportion of patients reporting "very good/excellent" in answer to the question in the PGAD questionnaire: "Considering all the ways in which your eczema affects you, indicate how well you are doing". Dupilumab treatment was well tolerated, with safety findings consistent with those previously reported in studies of dupilumab for the treatment of AD. Conclusions In the real-world PROSE registry, patients with moderate-to-severe AD experienced sustained improvement in disease control, symptoms, and quality of life up to 2 years after initiating dupilumab treatment. Safety data were consistent with the known safety profile of dupilumab. Trial Registration ClinicalTrials.gov identifier: NCT 03428646. Video abstract (MP4 20,717 kb) Infographic